Job Seeking Information Behaviours of Urban, Métis Youth - Dupont, Sarah (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Study of the information seeking behaviours of urban, Métis youth. Interviews address why Métis youth use certain tools, resources, and community programs to look for meaningful employment and how motivation affects the search process. Finds that talking to people is the most used method of information seeking. Étude des comportements de recherche d'information des jeunes métis en milieu urbain. Des entrevues permettent de clarifier pourquoi les jeunes métis utilisent des outils, des ressources et des programmes communautaires spécifiques pour chercher des emplois intéressants ainsi que les effets de la motivation sur le processus de recherche. Les conclusions démontrent que l'échange verbal est la méthode la plus utilisée.